Analysis of Creative Thinking Skills Based on Contextual Teaching and Learning in Physics Education Students - Heppy Sapulete; Izaak Hendrik Wenno; David Tuhurima; Ashari Bayu Prasada Dulhasyim (Postgraduate, University of Mataram, 2023)
This study aims to analyze students' creative thinking skills based on Contextual Teaching and Learning (CTL) in basic physics 1 subject, the physics education study program at Pattimura University. The research subjects were 22 students in semester 1 class of 2022. This research uses quantitative and qualitative descriptive research types. The research design used is a one shot case study. The instruments in this study are, 1) Observation sheets, to assess student creativity during the learning process. 2) Questionnaire sheet, to see student responses related to CTL learning and creative thinking skills. Data analysis in this study was carried out using quantitative descriptive analysis. The results of the study show that indicators of creative thinking skills have percentages, namely Elaboration of 60.61%, Flexibility of 57.58%, and Originality of 56.06%. The three indicators have percentages above 50% and the average final score for creative thinking skills for physics students class of 2022 is 58.08. So it can be said that creative thinking skills are sufficiently mastered by students. Student response data to learning using the CTL model was obtained at 73.27% in the satisfactory category. Based on the results of the study, it can be concluded that students' creative thinking skills based on CTL are sufficiently mastered by students